Patterns of Relationship and Sexual Behaviors in Mexican Adolescents and Associations with Well-being: A Latent Class Approach - Espinosa-Hernández, Graciela (J Adolesc, 2015)
To broaden our understanding of romance and sexuality during adolescence in Latin American countries, we used a person-oriented approach (latent class analysis) to examine classes marked by different patterns of romantic and sexual behaviors in Mexican adolescents. We found 5 classes: Inactive, (8.53%), Early stage (37.8%), Waiting class (27.5%), Physical (8.4%) and Committed (17.9%); but no group dating class. We also explored how these classes were associated with adolescents’ mental health and school performance. Middle school adolescents in the Committed class (high in romantic and sexual behaviors) had the highest level of depressive symptoms. Girls in the Inactive class and boys in the Physical class had the lowest level of symptoms. Adolescents in the Committed class also reported less academic motivation and achievement, whereas adolescents in the Inactive class reported higher motivation. This study expands our knowledge of adolescent romantic and sexual development in Mexico.